Factors Related to Occupational Safety and Health Implementation in Nurses at Tk II Putri Hijau Medan Hospital in 2018 - Lubis, Lidya Apriliana (Proceeding - Sari Mutiara Indonesia International Conference on Health, 2018)
Occupational health efforts are intended to protect workers in order to live a healthy life and be free from health problems and the adverse effects caused by work. Although the standards and regulations above have long been established, the implementation of OHS has not been maximized. This can be seen from the still high number of Occupational Accidents and Occupational Diseases in the world, especially in hospitals. The purpose of this study was to determine the factors associated with the implementation of occupational health and safety for nurses in Tk II Putri Hijau Medan Hospital in 2018. This type of research is an analytic study using a cross sectional design approach, namely a study by measuring independent and variable variables bound at the same time. The study sample consisted of 70 nurses. Sampling was done by proportional random sampling method.The results showed statistically that using the chi square test showed that the value of the variable working period (p = 0.237> 0.05), training (p = 0.223> 0.05) knowledge (p = 0.000 <0.05), attitude ( p = 0,000 <0,05), supervision (p = 0,008 <0,05), and SOP (p = 0,001 <0,05) which means that there is a significant relationship between knowledge, attitude, supervision and SOP with the implementation of safety and health work on the nurse while the variables of working period and training do not have a relationship.The conclusion of this study is that there is a significant relationship between knowledge, attitude, supervision and SOP with the implementation of occupational safety and health in nurses while the period of service and training there is no relationship. regularly and. It is recommended to the hospital so that nurses' knowledge is further enhanced by organizing socialization and education in the form of regular and periodic training.